2022
DOI: 10.1002/asi.24723
|View full text |Cite
|
Sign up to set email alerts
|

Gender and country biases in Wikipedia citations to scholarly publications

Abstract: Ensuring Wikipedia cites scholarly publications based on quality and relevancy without biases is critical to credible and fair knowledge dissemination. We investigate gender‐ and country‐based biases in Wikipedia citation practices using linked data from the Web of Science and a Wikipedia citation dataset. Using coarsened exact matching, we show that publications by women are cited less by Wikipedia than expected, and publications by women are less likely to be cited than those by men. Scholarly publications b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…That is, the scientific publication produc-tivity of female authors in these conditions will be lower than male authors. The results of this study confirm the results published in [42]. In particular, using coarsened exact matching, we show that publications by women are cited less by Wikipedia than expected, and publications by women are less likely to be cited than those by men.…”
Section: Resultssupporting
confidence: 90%
“…That is, the scientific publication produc-tivity of female authors in these conditions will be lower than male authors. The results of this study confirm the results published in [42]. In particular, using coarsened exact matching, we show that publications by women are cited less by Wikipedia than expected, and publications by women are less likely to be cited than those by men.…”
Section: Resultssupporting
confidence: 90%
“…Linguistic bias in terms of language abstraction and positivity can be observed, along with structural differences in metadata and hypertext links. In addition, citation practices reveal that female authors are cited less than expected, suggesting a preference for citing male publications (Zheng et al ., 2022). These biases may further marginalize female authors, especially in non-Anglophone countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study that revealed gender and country-based disparities is Zheng et al (2022). They examined Wikipedia's citation practices and found that women authors are cited less, particularly outside English-speaking countries.…”
Section: Gender Content Gapmentioning
confidence: 99%
“…Furthermore, Wikipedia can be the mirror of society but also, given its influence, it can amplify and deepen its inequalities and imbalances (Miquel-Ribé; Laniado, 2021). Illustrating this amplification, Zheng et al (2022) delves into Wikipedia's citation practices, unearthing disparities in citations to scholarly works linked to particular gender and nationality groups. Notably, women authors receive fewer citations than anticipated, indicating a bias toward citing male-authored publications.…”
Section: The Mirror Effectmentioning
confidence: 99%